Roskilde Festival - et socio-æstetisk landskab - Pedersen, Kristine Munkgård (K&K - Kultur og Klasse, 2014)
Roskilde Festival is the largest Danish music festival and provides an empirical basis for a discussion of the relationship between the social and aesthetic in contemporary cultural events. With the unfolding of the concept of social aesthetics, it becomes clear that the aesthetic potential of the festival is not limited to what is going on “on-stage”, but unfolds throughout the festival landscape. Based on ethnographical observation and phenomenological analysis of two different experience positions: “the panorama” and “the performative mass”, it is discussed how participation unfolds in the socio-aesthetic landscape of the festival. Through a review of the mass as an aesthetic phenomenon it is discussed how the aesthetic of participation succeed in transcending the dichotomy between subject and object ultimately leading to an aesthetic of dissolution.